Evaluation of Growth and Biochemical Markers for Salt Stress in Fenugreek (Trigonella foenum-graecum L.) - Palariya, Tilak; Akhtar, Md. Nadeem; Kumar, Santosh; Kumar, Amarendra (International Journal of Bio-resource and Stress Management, 2016)
Fenugreek (Trigonella foenum-graecum) also known as methi, is used both as herb (leaves) and as spice (seeds), also known for its medicinal values. The effects of salinity on plant growth are associated with low osmotic potential of soil solution (water stress), nutritional imbalance, specific ion effect (salt stress), or a combination of these factors. All of these cause adverse pleiotropic effects on plant growth and development at physiological, biochemical and molecular levels. A number of enzymes regulate intracellular H2O2 levels but catalase (CAT), total peroxidase (POD), ascorbate peroxidase (APX) and guaiacol peroxidase (GPOX) are known to play an important role. In the present study, an effort has been made to study the effect of salt stress on levels of different biochemical stress markers in seedlings of fenugreek cultivar (RMt-1), subjected to solution of -0.5, -0.7, -1.2, -1.7 Mega Pascal (MPa) osmotic potential. A decrease in seedling vigor and moisture content was observed when osmotic potential was increased from -0.5 Mpa to -1.7 MPa whereas Proline, H2O2, MDA,Total Chlorophyll,Chl a, Chl b and total phenolic content increased with the duration of stress. H2O2 metabolizing enzymes viz., APX, GR and GPOX showed a moderate increase in activity in comparison to SOD and POD, which showed a far greater increase in the activity, CAT activity declined with time. The results of these studies on fenugreek cultivar may be useful in elucidating tolerance mechanisms at the cellular level and may thus facilitate development of salt tolerant fenugreek cultivars.